The screenwriter's compass : character as true North - Gallo, Guy. (Boston : Focal Press, 2012)
Ever watch a movie, and despite great production value, fantastic action sequences, a great cast, etc, you come away thinking-I just didn't buy it. Chances are it was because you didn't care about the characters. Screenwriter's Compass presents a new way of approaching screenwriting, examining how effective screen storytelling must be grounded in the vivid imagining and presentation of character. Screenwriter's Compass will not offer formulas to follow but instead will give you the tools needed to chart your own path to screenwriting success. It details useful ways of thinking about writing, as well as practical ideas and concepts to help you discover the unique geography of your own imagination and navigate the problems posed by the struggle to express vision, agenda, and story. You'll learn how to root your writing in motivation and voice, to create screenplays that seduce and make your reader lean forward, and, most importantly, identify with your characters. * Guy Gallo brings well over twenty years of experience--both as a working screenwriter and as an instructor with a list of big-name students * ... including James Mangold (Girl Interrupted, Walk the Line), Greg Mottola (Superbad, Adventureland), Jeannine Dominy (Dangerous Beauty), and Christopher Zalla (Sundance Grand Jury 2007 for Sangre di mi sangre) * Shows screenwriters not just how to create characters, but how a screenplay emerges from these strong characters * Readers grow their understanding of their screenplays through Gallo's fresh interpretation of screenwriting.
FIRST THINGS Screenwriter's Compass Big Deal-You're Writing a Screenplay Gear Up Screenwriting Is Writing Craftsmanship GROUNDWORK Reading Theory Upsetting Aristotle Putting Aristotle to Work Character-Driven versus Plot-Driven Fable and Construct Turning Theory to Task GETTING READY Master Shot Screenplay Reading Screenplays Composition Creates Story On Outlines On Character Histories On Treatments On Adaptation FIRST DRAFT The Blank Page Scene and Action Description Camera Gestures and Paragraphing Being God Character Logic Hearing Voices Empathy Thinking of Structure Breaking a Block REVISION First Reader Looking Again for Logic Questions Challenges and Pitfalls On Expectation FINISHING Wrighting a Screenplay Screenplay Format Series of Shots Proofreading Submission GETTING READY AGAIN Passion and Purpose Happy Accident Intuition and Analysis Lessons.
Print version record.
Includes bibliographical references and index.
Keywords: Motion picture authorship; Screenwriters; Motion picture plays; Cinéma -- Art d'écrire.; Scénaristes.; Scénarios de cinéma.; screenplays; Motion picture authorship; Motion picture plays; Screenwriters